The Principal's Management in the Adiwiyata Program for Improving the Quality of Education at SMP Negeri 9 Samarinda - Dewi, Sulfiana; Dwiyono, Yudo; Akhmad; Komariyah, Laili; Nurlaili; Yahya, Masrur (EduLine: Journal of Education and Learning Innovation, 2025)
The importance of Adiwiyata is one of the elements that makes a school successful in creating a learning environment that supports improving the quality of education. The principal who also supports the success of the Adiwiyata program and improving the quality of education in schools. This study aims to describe the planning, organization, implementation, and evaluation of the principal's management in the Adiwiyata program to improve the quality of education. The approach to this research is qualitative with a case study method. The data collection method is carried out by observation, interviews and documentation. The data analysis method uses the pattern from Miles and Huberman with 4 stages, namely data collection, data reduction, data presentation and conclusions. The data validity check is carried out using source triangulation and technique triangulation. The planning carried out by the principal holds a coordination meeting related to the preparation of the school towards a national-level Adiwiyata school, identification of school environmental conditions, development of environmental care policies, formation of work teams, procurement of supporting facilities and infrastructure, and budget management. The organization is carried out in a structured manner and involves all school residents actively, starting from the formation of work teams to the formation of students who care about the environment. The implementation is structured and comprehensive through various activities that integrate environmental values into students' daily learning and life, such as cleaning activities, greening, waste management, water and energy conservation, and environmental-based learning applied in various subjects. The implementation of the Adiwiyata program has succeeded in supporting or improving the quality of education in terms of forming student character and the quality of good student learning has an impact on students' final grades and the quality of student graduates also has environmentally aware life skills. Evaluation and monitoring of the Adiwiyata program at SMP Negeri 9 Samarinda is carried out systematically by the principal through direct and indirect monitoring which is followed up with internal evaluation of the planning, implementation, and results of the program. Schools need to continue to develop supporting facilities and infrastructure for Adiwiyata activities and can develop the characteristics of the Adiwiyata program at SMPN 9 Samarinda.